Description of two new species of Nematoda: Litinium macramphida sp. nov. (Oxystominidae) and Cyartonema breviseta sp. nov. (Cyartonematidae) from the Yellow Sea, China - Wen, Guo; Huixin, Liang; Mengna, Wang; Chunming, Wang (Zootaxa, 2023)
Two new species of Nematoda, Litinium macramphida sp. nov. and Cyartonema breviseta sp. nov. are described from the Yelllow Sea. Litinium macramphida sp. nov. is characterized by body relatively long, inner and outer labial sensilla setiform with same length, amphideal fovea large and drop-shaped with amphideal aperture ovoid, spicules short and wide, gubernaculum simple and boat shaped, two precloacal supplements, and tail conical with rounded tip. Cyartonema breviseta sp. nov. is characterized by body short and slender, four cephalic sensilla papilliform, amphideal fovea circular and large, spicules curved and sickle-shaped, gubernaculum with dorsal-caudal apophysis and posterior end anteriorly hooked, and tail conical.